Hi,(adsbygoogle = window.adsbygoogle || []).push({});

So in my book they separate out a solution the heat equation into a function of x and a function of t and then separate the t and x dependencies, giving

[tex] -\frac{T''}{c^2T} = - \frac {X''}{X} = \lambda [/tex]

The book says that the proof is because

[tex] \frac {\partial \lambda}{\partial x} = 0[/tex]

and

[tex] \frac {\partial \lambda}{\partial t} = 0[/tex]

but if X = X(x) and T = T(t), how do you get zero out when you take d/dx and d/dt? Why don't you use the chain rule on -X''/X to get something like

[tex] \frac{\partial}{\partial x} (\frac{-X''}{X}) = (-\frac{X'''}{X} + \frac{X''(X')}{X^2}) [/tex]

thanks

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Separation of heat equation

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**